PWE-125 Stratification Of Hepatocellular Carcinoma Risk in Primary Biliary Cirrhosis by Biochemical Response to Treatment. (4th June 2013) - Trivedi, P; Li, K-K; Bruns, T; Shah, H; Tripathi, D; Shah, T; Neuberger, J; Hirschfield, G
Abstract : Introduction Aims: To review patterns of hepatocellular carcinoma (HCC) presentation in patients with primary biliary cirrhosis (PBC) in the context of disease severity and biochemical response to treatment. Methods: Patients with confirmed PBC seen at the Queen Elizabeth hospital (Birmingham) between September 1996 and December 2012 were identified, and a systematic retrospective chart review performed. Potential risk factors for the development of HCC were analysed using Fisher's exact test, multivariate logistic regression and Kaplan-Meier estimates (GraphPadv5.03). Results: Of 397 patients with PBC identified, 221 patients had developed cirrhosis, and 30 presented with or developed HCC (median age 68) over a 16 year period. Of all cases of HCC, 21 (70%) were identified through HCC surveillance programmes, and 19 patients presented within Milan criteria. In our practise, HCC was exclusively seen in the presence of cirrhosis. Using the cirrhotic non-HCC group as our comparator, male cirrhotics were more likely to develop HCC than female cirrhotics (OR 3.32; 95% CI 1.34–8.26; P = 0.012), and those with HCC were older at the time of diagnosis of cirrhosis (68 years vs. 57 years; P = 0.001). 67% (n = 20) in the HCC group and 76% (n = 145) of the non-HCC cirrhotic group were taking UDCA for > 1 year following diagnosis of PBC ( P = 0.21). Of the patients taking UDCA for > 1 year, 52% (n = 76) of the non-HCC cirrhotic group were biochemical responders according to the original Corpechot criteria compared with 20% (n = 4) of the HCC group ( P < 0.0001). Not taking or non-response to UDCA was significantly associated with the development of HCC (OR 4.54; 95% CI 2.24–9.20; P < 0.0001), and remained a significant risk factor after restricting the analysis to UDCA non-responders (OR 4.33; 95% CI 2.31–8.12; P < 0.0001). The cumulative hazard for HCC in cirrhotic UDCA non-responders was 0.18 at 5 years and 0.35 at 10 years after diagnosis of cirrhosis, but < 0.1 after 10 years in UDCA responders ( P = 0.003). The overall HCC incidence rate for cirrhotic patients with PBC was 3.4 cases/100 patient-years. When stratified by treatment response, UDCA responders had HCC rates of only 1 case/100 patient years, compared to 5 cases/100 patient-years in non-responders. Conclusion: Development of HCC in PBC is associated with a failure to respond to therapy with UDCA, older age at diagnosis of cirrhosis and male gender. The incidence rate for HCC development in cirrhotic patients responding to UDCA is arguably beneath the point at which cost-efficacy is likely met. Disclosure of Interest: P. Trivedi Grant/Research Support from: Wellcome Trust funded clinical research fellow, K.-K. Li: None Declared, T. Bruns: None Declared, H. Shah: None Declared, D. Tripathi: None Declared, T. Shah: None Declared, J. Neuberger: None Declared, G. Hirschfield: None Declared